Learning Jupyter 5 : Explore interactive computing using Python, Java, JavaScript, R, Julia, and JupyterLab, 2nd Edition /: Explore interactive computing using Python, Java, JavaScript, R, Julia, and JupyterLab, 2nd Edition. (2018) - Toomey, Dan
No abstract available